Global production and consumption of fast food and instant concentrates - Simakova, Inna Vladimirovna, 1977- (Advances in medical education, research, and ethics (AMERE) book series., 2022)
"This book offers a comparison of healthy food and fast food, presenting an ecological and hygienic assessment of the impact of fast food on the body in human observations and in vivo experiments, and answers if industrial food can serve as the basis for the nutrition of a modern person"--